Pemanfaatan Matematika Dasar Untuk Menghitung Kebutuhan Bahan Material Jalan Desa Orahili Tumori - Zebua, Friski Dermawan (CV. SINAR HOWUHOWU, 2025)
The development of road infrastructure is an important factor in supporting economic growth and community welfare. One of the key aspects of road construction is the accurate calculation of material requirements, which can help reduce construction costs and improve road quality. This study aims to evaluate the effectiveness of using basic mathematics in calculating road material needs. The research method used is descriptive-analytical with a quantitative approach, with samples taken from completed road projects in Indonesia over the last five years. Data was collected through documentation, interviews, and observations. The results show that the use of basic mathematics in calculating material requirements is highly effective and accurate, with 2 out of 3 projects analyzed showing calculations that closely match the actual material needs in the field. External factors such as soil conditions and design changes during the project can affect calculation accuracy. The study concludes that a good understanding of basic mathematics is essential for civil engineering professionals, and recommends enhancing basic mathematics education to support the efficiency of road construction projects in Indonesia.